Managing Schema Evolution in a federated spatial database system - Wu, Xiaoying (Curtin University, 2014)
In a FSDBS environment, database schemas are subject to changes and the management of these changes is complex and inefficient. In this research, an Automatic Schema Evolution (ASE) Framework has been developed in order to overcome the limitation of manual modifications of applications. The main components of ASE include: Schema Element Dependency (SED), Schema Mapping, Metadata Repository and Query/View Rewriting. Combined together, they enable the management of schema evolution in a FSDBS in an automatic and transparent manner.